Inborn error of metabolism patients after liver transplantation: Outcomes of 35 patients over 27 years in one pediatric quaternary hospital. Issue 5 (23rd January 2022) - Pritchard, Amanda Barone; Izumi, Kosuke; Payan‐Walters, Irma; Yudkoff, Marc; Rand, Elizabeth B.; Bhoj, Elizabeth
Abstract: Liver transplantation (LT) has been used for many years as a therapeutic option for certain inborn errors of metabolism (IEMs). Here we present one institution's 27 years of experience with LT in IEMs. Our objective is to assess the outcomes of IEM patients who have undergone LT, which we hypothesize to be generally successful for prevention of metabolic decompensation. A retrospective chart review was performed on patients with urea cycle defects, organic acidemias, and amino acidopathies who underwent LT at the Children's Hospital of Philadelphia. Thirty‐five patients with the following conditions have undergone LT: tyrosinemia (8), methylmalonic acidemia (7), maple syrup urine disease (6), citrullinemia (6), ornithine transcarbamylase deficiency (4), propionic acidemia (2), and argininosuccinate lyase deficiency (2). Average age at transplantation was 3.6 years. Three patients are now deceased. One patient suffered a metabolic stroke posttransplant. No episodes of metabolic decompensation have been noted. Thirty‐five patients received LT with generally favorable outcome. None sustained metabolic decompensation posttransplant. As has been reported previously, LT does not ameliorate pre‐existing developmental differences or risk to other organ systems. Further research is needed to aid in standardization of care and follow‐up, as most patients no longer follow with a geneticist.